Folate Intake May Affect Emotional Intelligence (P24-032-19). (13th June 2019) - Ramirez, Francisco; Krueger, Amy; Nedley, Neil; Hartman, John; Yew, Chen; LeBrun, Kendra
Abstract: Objectives: This observational explores the relationship between different intakes of folate and emotional intelligence (EQ). Methods: The data for the study came from n  = 5003 unique individuals that took the Depression and Anxiety Assessment Test (DAAT) an 85 question questionnaire. EQ was measured by a standardized mini EQ test included in the DAAT. Frequency of folate intake was self-reported and based on dietary and supplemental intake captured using the DAAT. According the answers, intake of folate intake subject were divided as high intake, average intake or poor intake. EQ measures five discrete attributes: knowing and managing one's own emotions, recognizing emotions in others, properly managing one's relationships, and motivation to achieve one's goals and physical health has an effect on it. Results: From n  = 5003 that took the test, n  = 2410 (48.1%) reported high folate intake and had a mean EQ of 113.2 (SD: 18) and median of 116. N  = 1246 (24.9%) reported average folate intake and had a mean EQ of 104.4 (SD: 18) and median of 104. Those with poor folate intake n  = 1347 (29.6%) had a mean EQ of 99.6 (SD: 17) and median of 98. With all subjects ( n  = 5003) considered together and folate intake translated into a numerical scale between 0 and 1 (poor intake: 1, average: 0.5, high: 0), Pearson's correlation revealed an r-value of 0.316 ( P  < 0.001) between folate intake frequency and EQ test score. Conclusions: It seems there is a weak relationship between the consumption of high-folate foods and EQ, though the mechanism for this effect is not known and requires further research. High EQ is important as it has been shown to greatly affect one's personal and professional achievement, better social intercourse and success in life. Funding Sources: Self funded.